Performance of LAI‐MODIS and the influence on drought simulation in a Mediterranean forest. Issue 3 (27th August 2013) - Chakroun, H.; Mouillot, F.; Nasr, Z.; Nouri, M.; Ennajah, A.; Ourcival, J. M.
ABSTRACT This study investigates the benefits and methodological issues to integrate weekly 1 km Leaf Area Index (LAI) Moderate Resolution Imaging Spectroradiometer (LAI‐MODIS) (MOD15A2) satellite product in a distributed water budget model over a Mediterranean forested ecosystem of about 2553 km2 for drought assessment at regional scale. The high overestimation of LAI‐MODIS compared to field measurements was corrected based on the calibration of high‐resolution Satellites Pour l'Observation de la Terre (SPOT) images combined with ground measurements. The LAI‐MODIS time series over the 2003 to 2009 period has been calibrated and integrated into a spatially explicit water budget model at the regional level using spatial information on vegetation, soil types and topoclimates. Actual LAI‐MODIS scenario was tested against temporal and spatial null models to assess for the benefits of the regional heterogeneity from MODIS and its intra‐annual and interannual variation in a water budget model. From water budget analyses at local and regional scales, we concluded that calibration of LAI‐MODIS images was mandatory to enhance the correlation coefficient between measured and simulated daily actual transpiration. We estimated daily bias in the resulting 'Water Stress Index' to be slightly affected between constant and seasonally‐varying LAI datasets. However, the interannual variability in LAI detected by MODIS followed LAI adjustments expected from the ecohydrological equilibrium hypothesis. This can significantly affect the simulated annual drought period features, so that integrating LAI‐MODIS spatial and temporal variability into water budget models for evergreen Mediterranean vegetation can be a useful dataset when carbon allocation schemes in dynamic vegetation models are lacking, but should be carefully calibrated particularly in transitions towards semi‐arid zones. Copyright © 2013 John Wiley & Sons, Ltd.